Migraine patients consistently show abnormal vestibular bedside tests - Maranhão, Eliana Teixeira; Maranhão, Péricles, Filho; Luiz, Ronir Raggio; Vincent, Maurice Borges (Arquivos de Neuro-Psiquiatria, 2016)
Migraine and vertigo are common disorders, with lifetime prevalences of 16% and 7% respectively, and co-morbidity around 3.2%. Vestibular syndromes and dizziness occur more frequently in migraine patients. We investigated bedside clinical signs indicative of vestibular dysfunction in migraineurs. ObjectiveTo test the hypothesis that vestibulo-ocular reflex, vestibulo-spinal reflex and fall risk (FR) responses as measured by 14 bedside tests are abnormal in migraineurs without vertigo, as compared with controls.MethodCross-sectional study including sixty individuals – thirty migraineurs, 25 women, 19-60 y-o; and 30 gender/age healthy paired controls.RESULTSMigraineurs showed a tendency to perform worse in almost all tests, albeit only the Romberg tandem test was statistically different from controls. A combination of four abnormal tests better discriminated the two groups (93.3% specificity).ConclusionMigraine patients consistently showed abnormal vestibular bedside tests when compared with controls.
Keywords: migraine; vertigo; bedside tests